The Brussels Free Trade Congress and International Association for Customs Reform - Hutton, Henry Dix (Dublin Statistical Society, 1857)
It is not necessary to dwell upon the benefits which must also result from the concentration of the efforts of distinct nations in the prosecution of objects involving the common interests of all; or upon the tendency which such co-operation must have to eliminate the jarring elements of traditional prejudice and national animosity, replacing these remains of a barbarous and retrograde system by conceptions which will gradually consolidate European peace, placing it under the protection of a strong, enlightened, and united public opinion. These are the noble objects for which the new " International Association for Customs Reform" is now working, and by virtue of which it claims the sympathy and aid of all who wish well to the cause of commercial liberty, and desire to substitute for a system which has been justly designated a state of industrial feudalism, one which, adopting mutual amity as its principle, and resting upon the invariable laws of social order, must result in the true welfare and progress of nations.
Read November 17th, 1856
Keywords: Brussels Free Trade Congress; International Association for Customs Reform; Customs reform; Free trade; 314.15